2002
DOI: 10.1034/j.1399-302x.2002.170307.x
|View full text |Cite
|
Sign up to set email alerts
|

In vivo induction of proinflammatory cytokines in mouse tissue by Porphyromonas gingivalis and Actinobacillus actinomycetemcomitans

Abstract: Periodontitis is a chronic inflammatory disease initiated by a multitude of bacteria. Persistent infection leads to generation of various inflammatory mediators, resulting in tissue destruction and osteoclastic resorption of the alveolar bone. This study describes a novel in vivo murine calvarial model to assess the effects of oral pathogens on the expression of three proinflammatory cytokines [interleukin (IL)-1beta, IL-6, and tumor necrosis factor (TNF)-alpha] which are involved in bone resorption. We chose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
54
0
5

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 35 publications
(35 reference statements)
1
54
0
5
Order By: Relevance
“…Our results revealed that P. gingivalis induces cytokine responses in our model, in accordance with the results reported by Sandros et al (39), who demonstrated that P. gingivalis can induce a strong cytokine response in primary cultures of pocket epithelium. The induction of cytokine expression following P. gingivalis infection was also reported for a mouse model (19).…”
Section: Discussionmentioning
confidence: 97%
“…Our results revealed that P. gingivalis induces cytokine responses in our model, in accordance with the results reported by Sandros et al (39), who demonstrated that P. gingivalis can induce a strong cytokine response in primary cultures of pocket epithelium. The induction of cytokine expression following P. gingivalis infection was also reported for a mouse model (19).…”
Section: Discussionmentioning
confidence: 97%
“…However, we cannot rule out the possibility that exposure to different cytokine concentrations further alters the PMN response to Ltx. Interestingly, Kesavalu et al (12) investigated the effects of oral pathogens on the expression of TNF-␣, IL-1␤, and IL-6 in the murine calvaria in situ and consequently showed that A. actinomycetemcomitans and P. gingivalis induced the expression of the gene for TNF-␣ at the highest level (TNF-␣ Ͼ Ͼ IL-1␤ Ͼ IL-6) in the calvaria. These observations suggest that these cytokines play an important role in pathogenesis in the periodontal bacterium-infected diseases, because it is well documented that these cytokines are potent factors in host inflammatory responses.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, nonfimbriated mutants display a reduced ability to induce periodontal disease in mice following oral inoculation (19). In this context, P. gingivalis FimA has been shown to induce proinflammatory cytokine release in macrophages (22) as well as inflammatory bone resorption (8,13).…”
mentioning
confidence: 99%